2016
DOI: 10.1007/s00265-016-2247-3
|View full text |Cite
|
Sign up to set email alerts
|

Predator avoidance and dietary fibre predict diurnality in the cathemeral folivore Hapalemur meridionalis

Abstract: Though numerous mammalian taxa exhibit cathemerality (i.e., activity distributed across 24-h cycle), this includes very few primates, exceptions being species from Aotinae and Lemuridae. Four non-mutually exclusive hypotheses have been proposed to explain ultimate determinants for cathemeral activity in lemurs: thermoregulatory benefits, anti-predator strategy, competition avoidance, and metabolic dietary-related needs. However, these have only been explored in the frugivorous genus Eulemur, with some species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 136 publications
0
11
0
Order By: Relevance
“…Furthermore, according to Donati et al (2006) and Eppley et al (2016), there are at least 4 hypotheses proposed to explain the determinants for cathemeral activity: thermoregulatory benefits, anti-predator strategy, competition avoidance and metabolic dietary-related needs. While based on Diete et al (2017), variation, fixity, and plasticity in activity patterns can be influenced by factors such as season and habitat (temporal resource availability).…”
Section: Activity Patternmentioning
confidence: 99%
“…Furthermore, according to Donati et al (2006) and Eppley et al (2016), there are at least 4 hypotheses proposed to explain the determinants for cathemeral activity: thermoregulatory benefits, anti-predator strategy, competition avoidance and metabolic dietary-related needs. While based on Diete et al (2017), variation, fixity, and plasticity in activity patterns can be influenced by factors such as season and habitat (temporal resource availability).…”
Section: Activity Patternmentioning
confidence: 99%
“…Donati and Borgognini-Tarli [2006b] found that the nocturnal activity of E. collaris correlated negatively with rainfall and humidity, but linked this association to the decrease in lunar luminosity due to cloud cover. Eppley et al [2017] did not find a strong association between the amount of rainfall and the ratio of diurnal to nocturnal activity in Hapalemur meridionalis, nor did Kappeler and Erkert [2003] in E. rufifrons. Many cathemeral primates have been shown to increase diurnal activity and decrease nocturnal activity during the wet season [Andrews and Birkinshaw, 1998;Curtis et al, 1999;Donati et al, 1999;Rasmussen, 1999;Kappeler and Erkert, 2003;Tarnaud, 2006;Eppley et al, 2015].…”
Section: Introductionmentioning
confidence: 55%
“…However, it is conceivable that bright nights may also offer some benefits that possibly outweigh the predation risk. For example, bright nights may allow an "early detection strategy" to avoid predators [see Gursky, 2003;Colquhoun, 2006;Fichtel, 2007;Prugh and Golden, 2014] and/or may improve foraging efficiency [Curtis et al, 1999;Donati et al, 1999;Valenta et al, 2016; see also Eppley et al, 2017]. Alternatively, sleeping at night could also be risky for lemurs (see, e.g., the predation of Propithecus diadema in their sleeping trees by Cryptoprocta ferox) [Wright et al, 1997].…”
Section: Effects Of Photoperiod and Moonlight On Cathemeral Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Southern bamboo lemurs (H. meridionalis) are medium-sized lemurs (albeit smallbodied primates) with an average body mass of 1.1 kg that exhibit a cathemeral activity pattern (Eppley et al 2015b(Eppley et al , 2015c(Eppley et al , 2017. This species is also known to feed heavily on a low-quality folivorous diet, the bulk of which is composed of various terrestrial grasses and sedges (Eppley et al 2011(Eppley et al , 2016a.…”
Section: Study Site and Speciesmentioning
confidence: 99%